Rethinking health accountability in Mozambique: Beyond donors and government? (Institute of Development Studies, 2018)
As I explored in my previous blog, the health sector and provision of health services in Mozambique is an uneven playing field. Since 1980 it has been shaped by a range of donors who have strategically positioned themselves according to their political weight and ability to contribute with ‘commodities’ and financial resources.  Although donors’ contributions […]
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; health / saúde

When a health system turns into a Tower of Babel: Mozambique's experience - Namburete, Denise (Institute of Development Studies, 2018)
Likened to the Tower of Babel legend, the Mozambican national health system speaks several languages and pursues a range of different interests, answering to a number of partners and other bilateral and multilateral actors who all have some kind of circumstantial and contextual interest. When the Paris Declaration on Aid Effectiveness was endorsed, Mozambique may […]
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde

Progress in Mozambique: Changes in the availability, use, and quality of emergency obstetric and newborn care between 2007 and 2012 - Augusto, Orvalho; Keyes, Emily E.; Madede, Tavares; Abacassamo, Fátima; de la Corte, Pilar; Chilundo, Baltazar; Bailey, Patricia E. (PLOS ONE, 2018)
Introduction Maternal mortality in Mozambique has not declined significantly in the last 10–15 years, plateauing around 480 maternal deaths per 100,000 live births. Good quality antenatal care and routine and emergency intrapartum care are critical to reducing preventable maternal and newborn deaths. Materials and methods We compare the findings from two national cross-sectional facility-based assessments conducted in 2007 and 2012. Both were designed to measure the availability, use and quality of emergency obstetric and neonatal care. Indicators for monitoring emergency obstetric care were used as were descriptive statistics. Results The availability of facilities providing the full range of obstetric life-saving procedures (signal functions) decreased. However, an expansion in the provision of individual signal functions was highly visible in health centers and health posts, but in hospitals, performance was less satisfactory, with proportionally fewer hospitals providing assisted vaginal delivery, obstetric surgery and blood transfusions. All other key indicators showed signs of improvements: the institutional delivery rate, the cesarean delivery rate, met need for emergency obstetric care (EmOC), institutional stillbirth and early neonatal death rates, and cause-specific case fatality rates (CFRs). CFRs for most major obstetric complications declined between 17% and 69%. The contribution of direct causes to maternal deaths decreased while the proportion of indirect causes doubled during the five-year interval. Conclusions The indicator of EmOC service availability, often used for planning and developing EmONC networks, requires close examination. The standard definition can mask programmatic weaknesses and thus, fails to inform decision makers of what to target. In this case, the decline in the use of assisted vaginal delivery explained much of the difference in this indicator between the two surveys, as did faltering hospital performance. Despite this backsliding, many signs of improvement were also observed in this 5-year period, but indicator levels continue below recommended thresholds. The quality of intrapartum care and the adverse consequences from infectious diseases during pregnancy point to priority areas for programmatic improvement.
Keywords: G - Mozambique / Moçambique; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

‘When helpers hurt’: women’s and midwives’ stories of obstetric violence in state health institutions, Colombo district, Sri Lanka - Perera, Dinusha; Lund, Ragnhild; Swahnberg, Katarina; Schei, Berit; Infanti, Jennifer J.; Darj, Elisabeth; Lukasse, Mirjam; Bjørngaard, Johan Håkon; Joshi, Sunil Kumar; Rishal, Poonam; Koju, Rajendra; Pun, Kunta Devi; et al. (BMC Pregnancy and Childbirth, 2018)
The paper explores how age, social position or class, and linguistic and cultural background intersect and place women in varying positions of control and vulnerability to obstetric violence in state health institutions in Colombo district, Sri Lanka. Obstetric violence occurs during pregnancy, childbirth and the immediate postpartum period; hence, it is violence that directly affects women. The authors aim to break the traditional culture of silence around obstetric violence and bring attention to the resulting implications for quality of care and patient trust in obstetric care facilities or providers.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Inverted State and Citizens’ Roles in the Mozambican Health Sector - Dias, Jose; Tomé, Tassiana (IDS Bulletin, 2018)
This article aims to understand the inversion of roles between the state and citizens, by exploring its historical roots and current implications for processes of social accountability in Mozambique, particularly in the health sector. This is a practice-based reflection grounded in the evidence collected through the implementation of Community Scorecards in the health sector in 13 districts of Mozambique. The evidence has revealed a transfer of responsibilities from local governance institutions and service providers to the communities; diluting the frontiers between the state and citizens’ duties and rights, resulting in the inversion of roles. This inversion results in the minimisation of the state’s performance of its duties and accountability in the health sector to respond to local communities’ needs, allegedly due to the lack of financial resources. It also leads to the overburdening of local communities, who assume the responsibility of meeting their own demands, risking participation fatigue.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; Important; L - english / inglês; Northern PEA; accountability / responsabilização; health / saúde

New Action Plan for Health Promotion in Cabo Delgado (Mozambique) (2018)
In Cabo Delgado - Mozambique, we are giving support to the Provincial Health Directorate (DPS-CD) in developing an essential tool for the promotion of health in the Province: The Action Plan for Health Promotion.
Keywords: *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; health / saúde

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Disrespectful and abusive treatment during facility delivery in Tanzania: a facility and community survey - Kruk, Margaret E; Kujawski, Stephanie; Mbaruku, Godfrey; Ramsey, Kate; Moyo, Wema; Freedman, Lynn P (Health Policy and Planning, 2018)
Although qualitative studies have raised attention to humiliating treatment of women during labour and delivery, there are no reliable estimates of the prevalence of disrespectful and abusive treatment in health facilities. We measured the frequency of reported abusive experiences during facility childbirth in eight health facilities in Tanzania and examined associated factors. The study was conducted in rural northeastern Tanzania. Using a structured questionnaire, we interviewed women who had delivered in health facilities upon discharge and re-interviewed a randomly selected subset 5–10 weeks later in the community. We calculated frequencies of 14 abusive experiences and the prevalence of any disrespect/abuse. We performed logistic regression to analyse associations between abusive treatment and individual and birth experience characteristics. A total of 1779 women participated in the exit survey (70.6% response rate) and 593 were re-interviewed at home (75.8% response rate). The frequency of any abusive or disrespectful treatment during childbirth was 343 (19.48%) in the exit sample and 167 (28.21%) in the follow-up sample; the difference may be due to courtesy bias in exit interviews. The most common events reported on follow-up were being ignored (N = 84, 14.24%), being shouted at (N = 78, 13.18%) and receiving negative or threatening comments (N = 68, 11.54%). Thirty women (5.1%) were slapped or pinched and 31 women (5.31%) delivered alone. In the follow-up sample women with secondary education were more likely to report abusive treatment (odds ratio (OR) 1.48, confidence interval (CI): 1.10–1.98), as were poor women (OR 1.80, CI: 1.31–2.47) and women with self-reported depression in the previous year (OR 1.62, CI: 1.23–2.14). Between 19% and 28% of women in eight facilities in northeastern Tanzania experienced disrespectful and/or abusive treatment from health providers during childbirth. This is a health system crisis that requires urgent solutions both to ensure women’s right to dignity in health care and to improve effective utilization of facilities for childbirth in order to reduce maternal mortality.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

GFF Civil Society Engagement Strategy Addendum - Adolescent and Youth (AY) - Global Financing Facility (Global Financing Facility, 2018)
The Global Strategy for Women’s, Children’s and Adolescents’ Health 2016-30 highlights the importance of adolescent health and well-being as being essential to achieving the Sustainable Development Goals (SDG) by 2030. For adolescents to survive, thrive and transform their societies, the global community needs to invest in their health and well-being. Today’s adolescents are well-positioned to mobilize their peers, advocate for increased resources for sexual and reproductive health and rights, influence their governments to invest in addressing their needs, and demand accountability for commitments related to their health and development. The Global Financing Facility (GFF) Civil Society Engagement Strategy (CSES) and related implementation plan provide a clear framework for civil society organizations’ (CSOs) contribution to the improvement of health outcomes through coalition strengthening, meaningful participation in multi-stakeholder country platforms responsible for coordinating health plans and their implementation,1 and coordinated action in support of the achievement of national sexual, reproductive, maternal, newborn, child and adolescent health (SRMNCAH) goals. Youth and adolescent led organizations should use the CSES as the basis for their engagement in the GFF processes both at the global and national levels. This Adolescent and Youth (AY) addendum to the CSES outlines a deliberate approach to ensuring youth representation in the processes led by the GFF Civil Society Coordinating Group2 (CSCG) to ensure their meaningful and active participation in the design, implementation, monitoring and evaluation of their country investment case.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; development partners / parceiros de cooperação; health / saúde; youth / juventude

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 Folheto (Brochure) - INS (2018)
O objectivo do IIM 2018 é disponibilizar as estimativas de indicadores demográficos e de saúde básicos, relacionados com a malária. As informações recolhidas através do IIM 2018 destinam-se a ajudar os decisores políticos e gestores do programa de controle de malária na avaliação e concepção de estratégias para melhorar a saúde da população do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA) 2015 - Ministério da Saúde- MISAU; Instituto Nacional de Estatística - INE; ICF (MISAU/Moçambique, INE, and ICF, 2018)
O presente relatório resume os resultados do Inquérito de Indicadores de Imunização, Malária e HIV/SIDA em Moçambique (IMASIDA 2015), conduzido pelo Instituto Nacional de Saúde (INS) do Ministério da Saúde (MISAU), em colaboração com o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através do Programa de Inquéritos Demográficos e de Saúde (Programa DHS). A assistência técnica adicional foi proporcionada pelo CDC (Centers for Disease Control and Prevention) dos Estados Unidos da América, através do seu escritório em Moçambique. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos para o Controlo da Malária (PMI), Fundo Global (FG-Rondas 8 e 9), Organização Mundial de Saúde (OMS), Fundo das Nações Unidas para a Infância (UNICEF), Aliança Internacional para a Saúde/Universidade de Washington (HAI/UW), Fundo das Nações Unidas para a População (FNUAP), Conselho Nacional de Combate ao HIV e SIDA (CNCS), através do seu Fundo Comum e Plano de Emergência do Presidente dos Estados Unidos para o Alívio da SIDA (PEPFAR), através do CDC.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Fast Facts from the 2018 Mozambique MIS - The DHS Program (2018)
The 2018 Mozambique Malaria Indicator Survey (IIM) provides population-based estimates on malaria indicators to inform strategic planning and program evaluation. The 2018 LMIS is the 6th survey to be conducted in Mozambique through The DHS Program.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza